2007
DOI: 10.1021/ma070051h
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diffusion of Entangled Linear and Circular DNA Molecules:  Dependence on Length and Concentration

Abstract: Self-diffusion coefficients (D) of DNA molecules of varying length and concentration were measured by tracking the Brownian motion of individual fluorescently labeled tracer molecules. Four possible cases were examined: linear tracer molecules surrounded by linear molecules (L-L), circular tracers surrounded by linears (C-L), linear tracers surrounded by circles (L-C), and circles surrounded by circles (C-C). With 6 and 11 kilobasepair (kbp) DNA D was largely insensitive to topology and varied consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 35 publications
(143 reference statements)
8
108
1
Order By: Relevance
“…In the case of DNA, we recently measured diffusion coefficients for entangled linear and relaxed circular molecules by tracking the Brownian motion of single molecules with fluorescence microscopy. 11 We found that the scaling of the diffusion coefficient with concentration and length was consistent with the reptation model for both topologies, but relaxed circular DNA diffused up to 7 times faster than linear DNA of the same length and concentration (45 kbp at 1 mg/mL). Thus, relaxed circular DNA appears to be less effective than linear DNA at producing restrictive entanglements.…”
Section: Introductionsupporting
confidence: 68%
“…In the case of DNA, we recently measured diffusion coefficients for entangled linear and relaxed circular molecules by tracking the Brownian motion of single molecules with fluorescence microscopy. 11 We found that the scaling of the diffusion coefficient with concentration and length was consistent with the reptation model for both topologies, but relaxed circular DNA diffused up to 7 times faster than linear DNA of the same length and concentration (45 kbp at 1 mg/mL). Thus, relaxed circular DNA appears to be less effective than linear DNA at producing restrictive entanglements.…”
Section: Introductionsupporting
confidence: 68%
“…The DNA concentration within phi29, like many other doublestranded DNA bacteriophages, is very high (∼0.5 g/mL), and one would expect excluded volume and chain entanglements to strongly restrict molecular motion (39,47,48). The effect of entanglements on the dynamics of polymers in melts and concentrated solutions has been successfully predicted by reptation models, in which polymer motion is restricted to a tube-shaped region parallel to the chain contour (39,49).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the conformation and relaxation of large polymer chains [62,63], as well as interaction with other chains [64], have been investigated in great detail by single-molecule techniques. Further, as cyclic and star-branched DNA are relatively easily obtainable, topology eff ects on polymer dynamics have also been investigated [65,66]. Th e study of large DNA is facilitated by its size-a fully labeled DNA helix is easily imaged by fl uorescence microscopy and changes in position and shape can be easily and precisely followed.…”
Section: Structure/conformation and Physics Of Non-conjugated Polymersmentioning
confidence: 99%